ANALISIS DAMPAK LALU LINTAS UNTUK MEMASTIKAN KELANCARAN ARUS TRANSPORTASI DI KABUPATEN MOROWALI UTARA - Budi Prasetyo; Sulbadana Sulbadana; Hamdan Rampadio (TADULAKO MASTER LAW JOURNAL, 2025)
This study examines the urgency of Traffic Impact Analysis (TIA) in development projects to ensure safety and prevent traffic congestion on roads, particularly in new autonomous regions such as North Morowali Regency. As a newly established regency, North Morowali faces significant challenges in improving land transportation infrastructure, which is essential for development and economic growth. However, the pace of development must be integrated with the principles of sustainable development that balance development needs, economic growth, and environmental preservation, including the impact on land use. The method used is empirical juridical, which combines normative analysis (written and unwritten law/secondary data) regarding Andalalin regulations with primary data from the field to see how Andalalin is implemented in law enforcement regarding building construction. The results and discussion show that development, which encompasses material and human aspects, often creates a dilemma between economic growth and negative impacts on the environment and social inequality, requiring attention to issues of income distribution, poverty, and justice. In the context of transportation, any change in land use (such as the construction of office buildings, hotels, or other public facilities) has the potential to generate new traffic that disrupts the smooth flow and safety of traffic. Andalalin is a crucial instrument for predicting the traffic impact of regional development. It determines the necessary traffic engineering and infrastructure improvements (e.g., provision of sufficient parking space). It aligns land use decisions with traffic conditions, in line with the principles of sustainable development. Therefore, Andalalin is a strategic and fundamental requirement that must be strictly implemented in North Morowali to ensure that physical infrastructure development can support economic acceleration without compromising safety, traffic flow, and environmental quality.